Digital behaviour change interventions to promote physical activity in overweight and obese adolescents: a systematic review protocol - Kassim, Puteri Shanaz Jahn; Muhammad, Noor Azimah; Abdul Rahman, Nur Faraheen; Mohd Sidik, Sherina; A. Essau, Cecilia; Azhar Shah, Shamsul (BioMed Central, 2022)
Background: With the increasing prevalence of obesity in youth, behavioural interventions to alter its modifable risk factors such as physical activity can support the management of this epidemic. Digital behaviour changes interventions (DBCI) such as mobile applications, websites and wearables have the potential to reach many adolescents to promote physical activity as its use may be more accessible, efective and engaging compared to traditional faceto-face approaches. However, there is insufcient evidence on their use at promoting physical activity amongst overweight and obese adolescents. This review aims to assess the efectiveness of DBCIs aiming to increase physical activity in overweight and obese adolescents (aged 10–19 years) and the behaviour change techniques used in these interventions. Methods: Electronic databases (MEDLINE, EMBASE, PsycINFO, CINAHL, Cochrane and Scopus) will be searched for English language studies from January 2000 to December 2022 using appropriate search terms relating to digital interventions, physical activity, adolescents and obesity. Experimental studies (either randomised or non-randomised controlled trials) assessing efects of DBCIs on physical activity behaviour, objectively or subjectively measured, in overweight and obese (body mass index [BMI] ≥ 85th percentile for age) adolescents will be eligible for inclusion. Intervention characteristics will be coded using the Template for Intervention Description and Replication (TIDieR) checklist and the BCT taxonomy v1. Risk of bias and the overall quality of the included studies will be assessed using Cochrane’s Collaboration’s tool and GRADE approach respectively. If the data allows, meta-analyses using random efect models will be conducted to assess the efects of DBCIs on physical activity. Discussion: The proposed systematic review will summarise the efectiveness of digital behaviour change interventions aiming to increase physical activity in overweight and obese adolescents, as well as adding new information on the behaviour change techniques used in these interventions. The fndings of this review will facilitate stakeholders.